Reading the world as a literacy practi- ce: a teacherʼs reflection - Chapetón, Claudia Marcela (Colombian Applied Linguistics Journal, 2004)
This article attempts to share with the reader a reading club program that was developed for a group of adults in situation of displacement in Bogotá, Colombia. It is framed in the context of forced internal displacement which is a critical social situation our country has been suffering lately and it is somehow, shaping our current, local teaching practices. The reflections presented in this article are focused both, on the critical theories of pedagogy and on my experience as teacher researcher in the creation and development of a Reading Club at “Red de Solidaridad Social”, Bogotá.